2019
DOI: 10.1177/0972558x19835371
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Levels at Two Different Phases of Menstrual Cycle: A Study on a Group of Bengali-speaking Hindu Ethnic Populations of West Bengal, India

Abstract: Aim: We aimed to find out the blood sugar levels at two different phases of menstrual cycle and the factors associated with the change in blood sugar level at these different phases. Material and methods: A total of 60 Bengali-speaking Hindu participants, who were married, aged between 30 and 45 years, have regular menstruation, and not diagnosed as diabetic, were selected for this study. A structured questionnaire was used to collect data on sociodemographic, menstrual, reproductive, and lifestyle variables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Blood glucose levels can fluctuate due to various factors, the most well-known being body composition 1 , diet 2 , 3 , and exercise 4 . Understanding these fluctuations is an essential part of maintaining a healthy lifestyle as they can indicate or obscure indicators of health issues including diabetes and vascular diseases 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Blood glucose levels can fluctuate due to various factors, the most well-known being body composition 1 , diet 2 , 3 , and exercise 4 . Understanding these fluctuations is an essential part of maintaining a healthy lifestyle as they can indicate or obscure indicators of health issues including diabetes and vascular diseases 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It may be explained as optimal vitamin D level is needed for normal FPG as it affects insulin production (33) . Moreover, FPG level may be affected by estrogen and progesterone levels as it may be lower in the premenstrual phase due to increase glucose consumption by cells or it may be higher in the luteal phase due to increased progesterone and decrease insulin sensitivity (34,35) . Additionally, hypoalbuminemia was significantly found in secondary T2DM osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Trout et al [ 72 ] reported high fasting glucose and low insulin sensitivity during the luteal phase, yet this finding was not significant. Dey et al [ 64 ] similarly reported increased blood glucose level in the same phase. Also, Denicoff et al [ 73 ] reported significant changes in glucose tolerance test in both luteal and follicular phases, but they denied PMS to be related to these changes.…”
Section: Dm and Pmsmentioning
confidence: 94%